A Sequential Therapeutic Hydrogel With Injectability and Antibacterial Activity for Deep Burn Wounds’ Cleaning and Healing - Wang, Sizhen; Li, Jie; Ma, Zhiqiang; Sun, Linhong; Hou, Lei; Huang, Ying; Zhang, Yunchang; Guo, Beibei; Yang, Feng (Frontiers in Bioengineering and Biotechnology, 2021)
As a severe clinical challenge, escharotomy and infection are always the core concerns of deep burn injuries. However, a usual dressing without multifunctionality leads to intractable treatment on deep burn wounds. Herein, we fabricated a sequential therapeutic hydrogel to solve this problem. Cross-linked by modified polyvinyl alcohol (PVA-SH/ε-PL) and benzaldehyde-terminated F127 triblock copolymers (PF127-CHO), the hydrogel demonstrated excellent mechanical properties, injectability, tissue adhesiveness, antibacterial activity, biocompatibility, and satisfactory wound cleaning through both in vitro and in vivo assays. Additionally, based on the conception of “sequential therapy,” we proposed for the first time to load bromelain and EGF into the same hydrogel in stages for wound cleaning and healing. This work provides a strategy to fabricate a promising wound dressing for the treatment of deep burn wounds with injectability and improved patients’ compliance as it simplified the process of treatment due to its “three in one” characteristic (antibacterial activity, wound cleaning, and healing effects); therefore, it has great potential in wound dressing development and clinical application.